Implementation and enhancement of risk management in frozen food Processing at UD. FFI Driyorejo Gresik - Andari, Laila Ayu; Kurniyanto, Ifan Rizky (Fakultas Pertanian Universitas Yudharta Pasuruan, 2025)
Introduction: Indonesian SMEs are vital for economic growth. UD. FFI Driyorejo Gresik, a frozen food SME, faces production planning and efficiency challenges due to demand fluctuations and absent risk management. This research identifies and prioritizes risks, recommending mitigation strategies. Methods: Qualitative data was collected via interviews at UD. FFI. The House of Risk (HOR) method was used to identify, assess, and prioritize risk agents, utilizing SCOR mapping, severity/occurrence assessments, and Pareto analysis. Results: Eighteen risk events and twenty-four risk agents were identified.